PUBLIC SECTOR: THE PHENOMENON OF EVALUATION AND ACCOUNTABILITY FOR RESULTS (Journal of Teleological Science, 2023)
The last few decades have witnessed a growing body of literature on performance measurement and accountability in the public sector (Kloot, 1999; Julnes & Holzer, 2001). The advent of New Public Management has made performance evaluation and, consequently, the accountability of public organizations in terms of results and performance, a key element in the process of modernizing public services. It is in this context that the relevance of this essay arises, intending to highlight the importance of performance evaluation and accountability. Throughout the article it is possible to better understand how both concepts arise in the Public Administration, as well as how they are defined.
Keywords: Public Sector; Evaluation; Accountability; New Public Management